4(2x-9)+5=-3(10-x)

Simple and best practice solution for 4(2x-9)+5=-3(10-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-9)+5=-3(10-x) equation:



4(2x-9)+5=-3(10-x)
We move all terms to the left:
4(2x-9)+5-(-3(10-x))=0
We add all the numbers together, and all the variables
4(2x-9)-(-3(-1x+10))+5=0
We multiply parentheses
8x-(-3(-1x+10))-36+5=0
We calculate terms in parentheses: -(-3(-1x+10)), so:
-3(-1x+10)
We multiply parentheses
3x-30
Back to the equation:
-(3x-30)
We add all the numbers together, and all the variables
8x-(3x-30)-31=0
We get rid of parentheses
8x-3x+30-31=0
We add all the numbers together, and all the variables
5x-1=0
We move all terms containing x to the left, all other terms to the right
5x=1
x=1/5
x=1/5

See similar equations:

| 7w-10=-38 | | 7a-(3a+6)=1 | | 5/8x-27=7 | | 5n=4n-1 | | 2x^​2-3x=-1 | | 5/3*p=30 | | 5x-11=7x-5=9 | | 2016x^2-x+2017=0 | | 456xY=68000 | | -2(y-4)+3y=15 | | -47+7m=2 | | (272x+2)=0 | | 96+80x-16x^2=96 | | 272x+2=0 | | 70(9+x)=1470 | | 2z+2z=8z-2 | | 7x+2=3×+14 | | 4x-1=×+5 | | y+4/5=1/4/5 | | y+4/5=14/5 | | (-9*2+x*2)=x+8 | | 6x+2/5=10 | | 4x-x-18=21 | | 141=(2×115)/(x+1) | | 14.2y-12.5=6.4y=13.7 | | 5x+10=2(x+8) | | 7x+5=-2, | | 23−4c=11 | | 2x+6/8=7 | | 23−4h=11 | | 50+3c=-31 | | 2x+6÷8=7 |

Equations solver categories